Differences of Malondialdehyde (MDA) Levels in Blood of Pulmonary Tuberculosis Sufferers with Diabetes Mellitus, Pulmonary Tuberculosis without Diabetes Mellitus and Healthy People in Medan - Eka Suhartika; Zainuddin Amir; Bintang Yinke Magdalena Sinaga; Putri C Eyanoer (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Background: The imbalance between oxidants and antioxidants in the body can increase Malondialdehyde (MDA) in patients with pulmonary TB and type 2 DM, which causes cell damage and worsens the disease. The body has a protective mechanism from damage caused by increased MDA through enzymatic antioxidants such as SOD and vitamin E. This study aimed to examine the difference in MDA levels in the blood of pulmonary TB patients with type 2 DM, pulmonary tuberculosis without type 2 DM and healthy people in Medan, Indonesia. Methods: This was an analytical study using a case-control approach by measuring MDA levels in pulmonary TB with type 2 DM patients, pulmonary TB patients and healthy people who were treated at H. Adam Malik General Hospital, Community Health Centers, and GP’s practice in Medan for 4 months. Blood samples were taken and examined using the ELISA kit. Data were then analyzed using the Kruskal Wallis and Mann Whitney tests. Results: There were 75 patients recruited in the study in which 45 were males (60%) and 30 were females (40%). The age group found the most was 31-40 years with normal BMI (76%). The highest MDA level was found in the TB+DM group at 12.42 nmol/ml compared to the TB patients (3.75 nmol/ml) and healthy people (3.01 nmol/ml). Conclusion: There were no statistically significant differences in MDA levels although there was a difference found in the MDA levels among the three groups with MDA level in TB+DM group was shown to be the highest.